FORMATION OF SCIENTIFIC SCHOOL OF KAZAKHSTAN international affairs: EUROPEAN VECTOR (International relations and international law Journal, 2016)
The article deals with international relations "as a scientific field - relatively young, but gaining power industry historical and political knowledge in our country. For a young country, which made in the early 90-ies of the first steps in foreign policy, diplomatic personnel were required, it was necessary understanding of what is happening in world politics and in the immediate external environment in Kazakhstan.
Keywords: European vector; OSCE; USA; OIC; SCO